Odgovornost države ali občine kot kontrolnega, večinskega delničarja oziroma družbenika v javnih podjetjih in podjetjih v javni lasti - Podgorelec, Peter (Podjetje in delo, 2016)
The Companies Act (Zakon o gospodarskih družbah - ZGD-1) lays down the rules on damage liability arising from the detrimental influence of third parties (Article 264). The controlling shareholder may also be defined as a third party. In the opinion of the author, the rules of law relating to groups of companies (group law) must also be applied in cases where state or municipality becomes the controlling shareholder.
Keywords: delničarji; država; gospodarske družbe; javna podjetja; nadzor; občine; odškodninska odgovornost